Impact of short and long exposure to cafeteria diet on food intake and white adipose tissue lipolysis mediated by glucagon-like peptide 1 receptor - Mattar, Pamela; Jaque, Cristian; Teske, Jennifer A.; Morselli, Eugenia; Kerr, Bredford; Cortés, Víctor; Baudrand, Rene; Perez-Leighton, Claudio E. (Frontiers in Endocrinology, 2023)
Introduction The modern food environment facilitates excessive calorie intake, a major driver of obesity. Glucagon-like peptide 1 (GLP1) is a neuroendocrine peptide that has been the basis for developing new pharmacotherapies against obesity. The GLP1 receptor (GLP1R) is expressed in central and peripheral tissues, and activation of GLP1R reduces food intake, increases the expression of thermogenic proteins in brown adipose tissue (BAT), and enhances lipolysis in white adipose tissue (WAT). Obesity decreases the efficiency of GLP1R agonists in reducing food intake and body weight. Still, whether palatable food intake before or during the early development of obesity reduces the effects of GLP1R agonists on food intake and adipose tissue metabolism remains undetermined. Further, whether GLP1R expressed in WAT contributes to these effects is unclear. Methods Food intake, expression of thermogenic BAT proteins, and WAT lipolysis were measured after central or peripheral administration of Exendin-4 (EX4), a GLP1R agonist, to mice under intermittent-short exposure to CAF diet (3 h/d for 8 days) or a longer-continuous exposure to CAF diet (24 h/d for 15 days). Ex-vivo lipolysis was measured after EX4 exposure to WAT samples from mice fed CAF or control diet for 12 weeks. . Results During intermittent-short exposure to CAF diet (3 h/d for 8 days), third ventricle injection (ICV) and intra-peritoneal administration of EX4 reduced palatable food intake. Yet, during a longer-continuous exposure to CAF diet (24 h/d for 15 days), only ICV EX4 administration reduced food intake and body weight. However, this exposure to CAF diet blocked the increase in uncoupling protein 1 (UCP1) caused by ICV EX4 administration in mice fed control diet. Finally, GLP1R expression in WAT was minimal, and EX4 failed to increase lipolysis ex-vivo in WAT tissue samples from mice fed CAF or control diet for 12 weeks. . Discussion Exposure to a CAF diet during the early stages of obesity reduces the effects of peripheral and central GLP1R agonists, and WAT does not express a functional GLP1 receptor. These data support that exposure to the obesogenic food environment, without the development or manifestation of obesity, can alter the response to GLP1R agonists. .